The Pattern of Proline, Glutamic Acid, and Leucine-Rich Protein 1 Expression in Chinese Women with Primary Breast Cancer. Issue 1 (January 2014) - Zhang, Yanzhi; Wang, Peng; Shi, Mumu; Sasano, Hironobu; Chan, Monica S.M.; Dai, Jiali; Guo, Lunshu; Liu, Ming; Wang, Xiaoyan; Ma, Ying; Wang, Lin
Background: Disparities of biomarkers' expression in breast cancer across different races and ethnicities have been well documented. Proline, glutamic acid, and leucine-rich protein 1 (PELP1), a novel ER coregulator, has been considered as a promising biomarker of breast cancer prognosis; however, the pattern of PELP1 expression in Chinese women with breast cancer has never been investigated. This study aims to provide useful reference on possible racial or ethnic differences of PELP1 expression in breast cancer by exploring the pattern of PELP1 expression in Chinese women with primary breast cancer. Methods: The expression of PELP1 in primary breast cancer samples from 130 Chinese female patients was detected by immunohistochemistry and correlated to other clinicopathological parameters; for comparison, the expression of PELP1 in 26 benign breast fibroadenomas was also examined. Results: The overall value of the PELP1 H-score in breast cancer was significantly higher than that in breast fibroadenoma (p<0.001). In our breast cancer patients, the ER/HER-2-positive group had significantly higher PELP1 H-scores than their negative counterparts (p=0.003 for ER and p=0.022 for HER-2); the Ki-67-high group also showed significantly higher PELP1 H-scores than the Ki-67-low group (p=0.008). No significant association between PELP1 H-scores and other clinicopathological parameters was found. Finally, the PELP1 H-score in breast cancers of the luminal B subtype was significantly higher than that in the triple negative subtype (p=0.002). Conclusion: Overexpression of PELP1 in Chinese women with primary breast cancer appears to be associated with biomarkers of poor outcome; these results are similar to other reports based on Western populations.